Viga composta com viga e laje pré-moldadas ligadas mediante nichos :análise via modelagem computacional - MELO, Matilde Batista (2009)
In structural system of composite beams with slab and beam, both precast, it is necessary that shear stress is transferred from the slab to the beam through the interface to assure the composite action between beam and slab. This study has the objective of assessing the behavior of composite beams with slab and beam precast connected by pockets. For this, it was developed a computational model based on the Finite Element Method using the commercial software DIANA® 9.3, which make possible the analysis of interaction between shear stresses transferred by interface to precast beam and shear stress on the precast beam due to vertical loading. In the analysis, the behavior of these beams was compared with the behavior of beams with continuous connection, usually employed. In addition, the type of beam-slab interface (with or without shear-key) was analyzed. It is tried from this analysis to confirm some models presented in the literature for design composite beams connected by pockets. Usually, the models used to design of reinforced concrete beams to shear are slightly modified to design the composite beams connected by pockets. The results show that, in fact, there is an increase on the shear stress of precast beam due to a discrete connection provided by pockets